Fabrication and electrical characterization of CdS quantum dots based solar cell - Farooq, W. A.; Atif, M.; Yakuphanoğlu, Fahrettin; Fatehmulla, Amanullah (Natl Inst Optoelectronics, 2016)
A quantum dots sensitized solar cell was fabricated and the electrical characterizations of QDSSC were investigated. The solar cell gives a short circuit current density of 1.3mA/cm(2) and an open circuit voltage of 0.38V under AM1.5. The capacitance-voltage, conductance-voltage and series resistance-voltage characteristics of the solar cell were measured in a wide range of frequencies for the QDSSC application. The photovoltaic performance of the QDSSC can be improved using various chemicals.
Keywords: Quantum Dot Sensitized Solar Cells (QDSSCs); Photovoltaic properties; Impedance spectroscopy